Firm heterogeneity, market relatedness and geographical diversification of export from China - Hu, Xuqian; He, Canfei (ERDKUNDE, 2020)
Based on traditional international theories, exporters always expand their export markets in an incremental way. However, there are many exporters who do not obey the traditional path and enter foreign markets at the beginning of their internationalization, so called ‘born globals (BGs)’. It seems that the BGs are more path-breaking, but the relative influence of local export network on both types of exporters remains an open question. Using firm-market level database of Chinese custom statistics during 2002-2011, we confirm that local export network of markets facilitates firms including BGs to enter the markets that are more related to the network. And the BGs even benefit more from the local export network of markets than traditional exporters (TEs).